ISLAMIC IDENTITY VERSUS CITY/PLACE BRANDING - Mandour, M. Alaa (Journal of Islamic Architecture, 2012)
Is a brand a product, a service, or a company? Is it a logo, a marketing strategy or an attitude? As globalization intensifies, places increasingly compete with other places for attention, influence, markets, investments, businesses, visitors, residents, talent and events. And competition is no longer restricted to the well-known places down the road, over the hill or across the water. Places now compete with cities, regions and countries halfway around the world. Places are increasingly getting caught off guard by unpredicted and apparently rapid shifts in competition and abruptly lose their historic purpose or their competitive edge, be it economic, social or cultural. Culture fills our cities, regions, nations and even our rural landscapes with spiritual content. Our places are an expression of who we are and what we value and they are ruthless in projecting the bad alongside the good. In its widest sense culture includes art, design, education, science, religion and sport. In the context of place branding it is the manifestation of our beliefs, values, customs and behaviors. Merging culture to brand within our city tissue is an essential part of the morphology within its spaces. This paper is trying to discuss the contribution of Islamic culture to a place brand; Relationship between culture and identity, image, visual identity etc. in the context of place branding; Impact of culture on brand equity; Developing cultural brand assets to brand places and how should we value and evaluate culture in the context of place branding?Â  Also will try to find answers to the following: Do we have a precise understanding of how Islamic culture adds value to or devalues a place? Do we have a methodology for capturing the value of our Islamic culture to places? And, can this culture be developed with the intent to create better places and place brands?Â  Â